Independent prognostic value of tumor deposits in stage III colorectal cancer: a large-scale systematic review and meta-analysis - Liao, Jiankun; Qin, Haiquan; Meng, Linghou; Wang, Wentao; Wei, Haotang; Mo, Xianwei (Journal of Gastrointestinal Oncology; Vol 17, No 3 (June 29, 2026): Journal of Gastrointestinal Oncology, 2026)
Background: XXXXXXXXXXXXXXXXXXXXXXXXXXXXXXXXXXXXX. The study aims to systematically evaluate the prognostic value of tumor deposits (TDs) in patients with stage III colorectal cancer (CRC), clarify their impact on long-term oncologic outcomes, and provide evidence-based medicine to optimize CRC tumor-node-metastasis (TNM) staging and guide individualized treatment decisions.Methods: A comprehensive literature search was conducted across PubMed, Embase, Cochrane Library, ScienceDirect, and Web of Science databases to identify studies investigating the association between TDs status and prognosis in stage III CRC patients, published from database inception to December 31, 2025. Two independent researchers performed literature screening, data extraction, and quality assessment. Statistical analyses were conducted using R software (version 4.4.1). The primary outcomes were 5-year overall survival (OS) and 5-year disease-free survival (DFS).Results: A total of 18 high-quality studies involving 236,867 patients were included, comprising 16 non-randomized controlled studies and two randomized controlled trials (RCTs). Meta-analysis results demonstrated that patients with both TDs positivity and lymph node positivity (TD+LN+) had significantly poorer 5-year OS compared to those with TDs negativity but lymph node positivity (TD−LN+) [relative risk (RR) =1.58, 95% confidence interval (CI): 1.50–1.65, I2=75.3%] and those with TDs positivity but lymph node negativity (TD+LN−) (RR =1.39, 95% CI: 1.30–1.48, I2=67.2%). Additionally, TD+LN− patients exhibited significantly inferior 5-year OS relative to TD−LN+ patients (RR =1.21, 95% CI: 1.06–1.38, I2=76.6%). Consistent prognostic differences were observed for 5-year DFS. Subgroup analyses further revealed that TD+LN− patients had significantly worse 5-year OS (RR =1.39, 95% CI: 1.18–1.64, I2=68.5%) and 5-year DFS (RR =1.44, 95% CI: 1.20–1.73, I2=40.3%) compared to TD−LN1 patients. However, no statistically significant differences were noted in 5-year OS (RR =0.89, 95% CI: 0.70–1.13, I2=80%, P=0.33) or 5-year DFS (RR =0.90, 95% CI: 0.66–1.23, I2=57.0%, P=0.51) between TD+LN− and TD−LN2 patients.Conclusions: This study confirms that TDs are independently associated with worse prognosis in patients with stage III CRC. TD+LN+ patients exhibit significantly poorer long-term survival (5-year OS and DFS) compared to those with lymph node positivity alone, while TD+LN− (N1c stage) patients have a prognostic risk intermediate between N1 and N2 stages. The current TNM staging system fails to fully integrate the prognostic value of TDs, particularly in lymph node-positive patients. We recommend optimizing the staging schema and incorporating TDs status into clinical risk stratification to develop individualized intensive treatment strategies for high-risk TDs-positive patients, thereby improving patient outcomes.